Frequency dependence of coordinated pupil and eye movements for binocular disparity tracking - Balaban, Carey D.; Nayak, Neil S.; Williams, Erin C.; Kiderman, Alexander; Hoffer, Michael E. (Frontiers in Neurology, 2023)
Coordinated alignment of the eyes during gaze fixation and eye movements are an important component of normal visual function. We have previously described the coordinated behavior of convergence eye movements and pupillary responses using a 0.1 Hz binocular disparity-driven sine profile and a step profile. The goal of this publication is to further characterize ocular vergence-pupil size coordination over a wider range of frequencies of ocular disparity stimulation in normal subjects. Binocular disparity stimulation is generated by presentation of independent targets to each eye on a virtual reality display, while eye movements and pupil size are measured by an embedded video-oculography system. This design allows us to study two complimentary analyses of this motion relationship. First, a macroscale analysis describes the vergence angle of the eyes in response to binocular disparity target movement and pupil area as a function of the observed vergence response. Second, a microscale analysis performs a piecewise linear decomposition of the vergence angle and pupil relationship to permit more nuanced findings. These analyses identified three main features of controlled coupling of pupil and convergence eye movements. First, a near response relationship operates with increasing prevalence during convergence (relative to the ‘baseline’ angle); the coupling is higher with increased convergence in this range. Second, the prevalence of ‘near response’-type coupling decreases monotonically in the diverging direction; the decrease persists after the targets move (converge back) from maximum divergence toward the baseline positions, with a minimum prevalence of near response segments near the baseline target position. Third, an opposite polarity pupil response is infrequent, but tends to be more prevalent when the vergence angles are at maximum convergence or divergence for a sinusoidal binocular disparity task. We suggest that the latter response is an exploratory ‘range-validation’ when binocular disparity is relatively constant. In a broader sense, these findings describe operating characteristics of the near response in normal subjects and form a basis for quantitative assessments of function in conditions such as convergence insufficiency and mild traumatic brain injury.